Integrating Critical Thinking into Extension Programming #3: Critical Thinking Style - Alexa J. Lamm (EDIS, 2015)
This 3-page fact sheet is the third in the Integrating Critical Thinking into Extension Programming series. It introduces the concept of critical thinking style and describes the two styles of critical thinking. Written by Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, April 2015.